Boundary Issue in the Terminosystem - Mahmudova Dilafruz (International Journal on Human-Computing Studies, 2022)
It is understood that the terms are not always used in a narrow range; they can also be used extensively in speech when the need arises. It can be concluded that terms approaching the boundary of the terminosystem have a common denominator with words. They can be actively used as common words in speech. Terms from the center of the terminosystem represent the sign of specificity. They can only be used in a specific field of science. For example, the terms that are close to the boundaries of the terminology of the chemical industry are: coal, cast iron, silver, lime, copper, mercury, and so on. Terms that have specificity and are used in a narrow range can include: hydroxide, litmus, molecular weight, insecticide.